2009
DOI: 10.1073/pnas.0710416106
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrosyliron complexes and the mechanism(s) of cellular protein nitrosothiol formation from nitric oxide

Abstract: Nitrosothiols (RSNO), formed from thiols and metabolites of nitric oxide (•NO), have been implicated in a diverse set of physiological and pathophysiological processes, although the exact mechanisms by which they are formed biologically are unknown. Several candidate nitrosative pathways involve the reaction of •NO with O 2, reactive oxygen species (ROS), and transition metals. We developed a strategy using extracellular ferrocyanide to determine that under our conditions intracellular protein RSNO formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
221
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(241 citation statements)
references
References 44 publications
14
221
3
1
Order By: Relevance
“…3C). S-nitrosation of C151 presumably proceeds by transnitrosation, possibly via dinitrosyliron complexes (26).…”
Section: Molecular Basis For the Reactivity Of C151 With Electrophilementioning
confidence: 99%
“…3C). S-nitrosation of C151 presumably proceeds by transnitrosation, possibly via dinitrosyliron complexes (26).…”
Section: Molecular Basis For the Reactivity Of C151 With Electrophilementioning
confidence: 99%
“…Studies exploring the S-nitrosylation of proteins in cells indicated that more than 50% of the cellular formation of protein S-nitrosocysteine is derived by dinitrosyliron complexes (7). Within the liver S-nitrosoproteome, 13 Snitrosylated cysteine residues, which are directly involved in the chelation of metal ions, were identified (Table S3).…”
Section: S-nitrosylation Occurs On Cysteine Residues Adjacent To Flexmentioning
confidence: 99%
“…The identification of in vivo S-nitrosylated proteins has indicated that not all reduced cysteine residues and not all proteins with reduced cysteine residues are modified, implying a biased selection. Several biological chemistries have been proposed to account for the S-nitrosylation of proteins in vivo (1,7,8). Broadly, these include (i) oxidative S-nitrosation by higher oxides of NO, (ii) transnitrosylation by small molecular weight NO carriers such as S-nitrosoglutathione or dinitrosyliron complexes, (iii) catalysis by metalloproteins, and (iv) protein-assisted transnitrosation, as elegantly documented for the S-nitrosylation of caspase-3 by S-nitrosothioredoxin (9, 10).…”
mentioning
confidence: 99%
“…These effects are explained by the reactivity of NO with iron in iron-sulfur clusters, e.g. in the electron transport chain and other pools (1,3). The high affinity of NO for Fe(II) results in the interaction of NO with iron-sulfur clusters in proteins.…”
mentioning
confidence: 99%